Characterization of a diverse okra (Abelmoschus esculentus L. Moench) germplasm collection based on fruit quality traits - Yildiz, Mehtap; Sirke, Sibel Turan; Koçak, Metin; Mancak, Ibrahim; Özkaya, Aslihan Agar; Abak, Kazim; Özkaya, Okan; Cavagnaro, Pablo (MDPI, 2025)
Okra is an important dietary component of many Asian countries, providing high levels of dietary fiber, phytonutrients (e.g., antioxidant vitamins and pigments), and essential minerals. Evaluation of okra germplasm collections can improve the curation of genebanks and help identify superior materials for breeding. In this study, 66 okra accessions from diverse geographical origins were characterized based on fruit quality traits, including fruit fresh (FFW) and dry weights (FDW), dry matter (DM), diameter, length, and diameter of the fruit peduncle; concentration of vitamin C, chlorophyll a and b, and total chlorophyll; and color-chroma values. Significant (p < 0.05) and substantial variation was found among the accessions for all traits. Mean FFW and FDW varied nearly three-fold, with ranges of 3.76–9.99 g and 0.43–1.34 g, respectively, with a range in DM content of 10.5–19.4%. Vitamin C and total chlorophyll content varied 6.4- and 8.3-fold, with ranges of 12.8–82.8 and 1.07–8.91 mg/100 g fw, respectively, with substantial variation also observed in chlorophyll composition. Significant positive correlations were found between vitamin C and total and subtypes of chlorophyll levels (r = 0.29–0.32), whereas the strongest correlations were between FFW and FDW (r = 0.88) and between total chlorophyll and chlorophyll subtypes a and b (r = 0.90–0.95). Additionally, a dendrogram constructed based on these phenotypic data grouped the accessions in general agreement with their geographical origins and fruit traits. Overall, our results revealed broad phenotypic diversity in the evaluated germplasm, which is exploitable in okra breeding programs aimed at increasing fruit quality and nutraceutical value.